بارگاہِ نبوت ﷺ میں وفودِ عرب کی اکرام نوازی اور عطایا: دعوتِ اسلامی کی حکمتِ عملی کا تحقیقی جائزہ: Hospitality and Grants to Arab Delegations in the Prophetic Court: A Research Study on the Strategic Approach to Islamic Da‘wah in the Prophetic Biography (Al-Aasar, 2025)
The arrival of Arab delegations at the court of Prophet Muhammad (peace be upon him) following the conquest of Makkah and the Battle of Ḥunayn played a pivotal role in the expansion and consolidation of Islam. These delegations, comprising mainly tribal chiefs and influential leaders, served as essential channels for the propagation of Islamic teachings within their respective tribes. The ninth year of Hijrah, known as ‘Ām al-Wufūd or the “Year of Delegations,” witnessed unprecedented influxes of these groups seeking allegiance, guidance, and negotiation. This study examines the Prophetic strategy of honoring and hosting these delegations through hospitality, education, and the distribution of grants and gifts (‘Aṭāyā). By providing material incentives alongside moral and religious instruction, the Prophet (peace be upon him) not only fostered goodwill but also ensured that these leaders became active agents of Da‘wah within their communities. Such practices encouraged entire tribes to embrace Islam, often following the conversion of a single influential leader. The research highlights the wisdom underlying this approach, emphasizing that the provision of grants and honors was not mere generosity but a deliberate and strategic measure to strengthen Islam’s social, moral, and political foundations. By analyzing historical sources, Qur’anic injunctions, and Prophetic traditions, this study demonstrates that the practice of honoring delegations and granting incentives was instrumental in stabilizing the early Muslim community and in expanding Islam’s influence across the Arabian Peninsula. This model provides valuable insights for contemporary Da‘wah efforts, illustrating the significance of strategic engagement, respect, and incentive-based propagation in religious and social leadership.